Let \(2ab=c^2. Then (a+b)^2 - 2ab = a^2 + b^2 =(a+b)^2 - c^2 = (a+b+c)(a+b-c)\), which is not prime because a+b-c cannot be equal to 1(a and b are bigger or equal to 2).

\(a + b - c\) is not equal to 1 or -1, because we will get \(a + b \pm 1 = c\) and then by squaring both of the sides we will get \(a^2 + b^2 + 1 + 2ab \pm2a \pm 2b = 2ab\), which is impossible.

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestLet \(2ab=c^2. Then (a+b)^2 - 2ab = a^2 + b^2 =(a+b)^2 - c^2 = (a+b+c)(a+b-c)\), which is not prime because a+b-c cannot be equal to 1(a and b are bigger or equal to 2).

Log in to reply

\(a + b - c\) is not equal to 1 or -1, because we will get \(a + b \pm 1 = c\) and then by squaring both of the sides we will get \(a^2 + b^2 + 1 + 2ab \pm2a \pm 2b = 2ab\), which is impossible.

Log in to reply